Using Data Collection Applications in Early Childhood Settings to Support Behavior Change. Issue 3 (September 2021) - Riggleman, Samantha
Social–emotional development in early childhood (EC) is an important factor to their later development and adjustment. While all young children display unwanted behaviors at some time during development, challenging behaviors that occur across settings and over a period of time should be identified and intervened; thus, data collection efforts need to be efficient and accurate as time can be a barrier. There are currently applications for children in a K–12 setting that can be used to collect data and share positive behavior support plans; however, they may not necessarily be tailored to the EC population. A variety of data collection apps will be discussed as they relate to identifying a behavior to data collection skills. Suggestions will be given on what apps should contain for data collection and how to make them applicable to EC settings as well as collaborating with multiple professionals.